The Creative Process of Choreographing Galombang Dance by Citra Kembara Studio Padang City - Kasi Amanda; Susmiarti (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2024)
This research aims to describe and describe the creative process of choreographing Galombang dance in Citra Kembara Studio in Padang City. This research uses descriptive method of qualitative research. The object of research is Galombang dance in Sanggar Citra Kembara Kota Padang and focused on the creative process of its choreography. Data collection is done through literature study, observation, interviews and documentation.  With the results of interviews and documentation can determine data analysis by using triangulation techniques that the results of observations can be compared. The results of the research as a whole illustrate that Galombang dance is performed in groups, with 11 dancers (4 men, 7 women), where the function of Galombang dance is to welcome guests and is performed in an open field. Galombang dance is danced by teenage and adult dancers ranging in age from 18-30 years. The creative process of choreographing Galombang dance at Citra Kembara Studio in Padang City is formed from the following stages:  (1) Exploration Stage, (2) Improvisation Stage, (3) Formation Stage. The description and description of this Galombang Dance of Citra Kembara Studio are; (1) Galombang dance form consists of ideas, dancers, and movements, (2) Galombang dance parts consist of the beginning, middle, and end parts, (3) The names of Galombang dance movements are Gerak Sambah I, opening movements, sambah II movements, welcome movements, thank you movements, creation movements, and siriah serving movements, (4) Musical Instruments used bansi, drums, sarunai, tasa, and talempong, (5) Makeup used beautiful makeup for women natural makeup for men. Galombang dance costumes for women use baju kurung, songket skirt, ikat pingang, and shawl, while for men black silat clothes, black pants, sideways. Head makeup for women: sunting, bamboo skewers, bun caps, lame, laca, flowers, necklaces. Men only wear destar. The property used in Galombang dance is Carano.